2010
DOI: 10.1177/0961203310375263
|View full text |Cite
|
Sign up to set email alerts
|

De novo infantile primary antiphospholipid antibody syndrome

Abstract: Most autoimmune diseases are rare in infants. Early onset can represent an extreme phenotype arising from strong genetic predisposition relatively independent of environmental influence. Alternatively, neonatal autoimmunity can arise from transplacental passage of maternal pathogenic IgG autoantibodies. Distinguishing between these possible explanations is crucial for determining the prognosis in the specific patient, and has important implications for understanding pathogenesis. We report a case of neonatal t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…In particular, primary autoimmune disease in the neonate is almost unheard of, and there are no retrospective or prospective series of such patients described in the literature, although very rarely a case report will appear [114]. Most neonatal autoimmune disease is associated with a passive process involving transplacental transfer of maternal antibodies targeting fetal or neonatal tissue.…”
Section: Summary and Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…In particular, primary autoimmune disease in the neonate is almost unheard of, and there are no retrospective or prospective series of such patients described in the literature, although very rarely a case report will appear [114]. Most neonatal autoimmune disease is associated with a passive process involving transplacental transfer of maternal antibodies targeting fetal or neonatal tissue.…”
Section: Summary and Discussionmentioning
confidence: 93%
“…While most of the syndromes described above are believed to be related to transplacental transfer of maternal antibodies, several case reports of de novo primary antiophospholipid syndrome in a neonate or infant have been reported [114]. In one case presented in 2010, there were antibodies to both cardiolipin and b2-Glycoprotein1 detected in a neonate with a thrombotic stroke.…”
Section: Primary Neonatal Autoimmune Diseasesmentioning
confidence: 95%
See 1 more Smart Citation
“…We observed that 43% of the patients in this study had seizures as a major clinical manifestation and that these were usually secondary to cerebral artery infarcts. Thus, epilepsy development was unusual [10, 11, 1417, 20, 21]. Alshekaili et al [17] described the case of a 5-day-old newborn who had a reduction in spontaneous right limb movements.…”
Section: Discussionmentioning
confidence: 99%
“…aPL are a recognised prothrombotic risk factor associated with acute ischaemic infarction 3. Most autoimmune diseases are rare in infants, and in the neonatal period, autoimmunity is related to transplacental passage of maternal IgG autoantibodies 4. The rate of stroke is higher in the primary aPS patients, who are also younger at presentation 3.…”
Section: Introductionmentioning
confidence: 99%